Dampak Pandemi Covid-19 Terhadap Usaha Mikro Kecil Menengah (UMKM) Di Kota Ternate Studi Kasus Umkm Di Kelurahan Mangga Dua - Narilah A. Tuara; Akmal Lule; Rahmat Manuasi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The COVID-19 pandemic has caused a decline in turnover or income for restaurant business traders and basic food businesses in Mangga Dua Village, Central Ternate District. This study aims to determine how big the impact of COVID-19 on MSME actors, restaurant traders and basic food traders in Mangga Dua Village and how the Ternate City Government intervened against MSME actors. The research method used is descriptive qualitative method, using secondary data sources and the results of direct interviews with restaurant traders and basic food traders. buy the community or consumers for the goods traded. There have been efforts by business actors to increase their income by utilizing social media technology, but this has not been done optimally. In addition, this study provides recommendations for MSME survival strategies, namely trading through the use of digital marketing as an additional service to consumers and optimizing marketing relationships and maintaining products and maintaining existing customers.